Daya Saing Usaha Mikro Kecil Menengah di Kawasan Bukit Lawang - Sinurat, Tio (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2024)
Tourism is one of the most important economic industries in several countries, including Indonesia. Bukit Lawang in North Sumatra has become one of the tourist attractions that has attracted a lot of attention in recent years. The aim of this research is to improve and expand SME and analyze competition in Bukit Lawang. This research methodology includes surveys and interviews. Based on these findings, Bukit Lawang has high potential as an ecotourism destination because of its natural beauty, especially the beautiful tropical rainforest and rare orangutan population. However, there are a number of obstacles that must be overcome by the government. The research results show that the tourism industry in Bukit Lawang has a level of competition in SME, many competitors compete with each other in terms of price and quality of products being marketed. This shows the need for marketing strategies and efforts to retain local and foreign tourists